PENGARUH PESAN GO GREEN, NO PLASTIC PADA KAMPANYE UPN VETERAN JAKARTA TERHADAP SIKAP PENGGUNAAN KEMASAN PLASTIK DI LINGKUNGAN KAMPUS PADA MAHASISWA UPN VETERAN JAKARTA - Qhori Anandra (2020)
The background of the number of uses of plastic packaging every year is always increasing and the Indonesian government implemented a greening program, eventually making UPNVJ launch a go green, no plastic program. The purpose of this research is to find out there is an influence of the message from the Go Green, No Plastic Campaign implemented by the Jakarta "Veteran" National Development University in changing the attitude of not using plastic packaging in the campus environment for UPNVJ students. Theories used Theory of Elaboration Likelihood. The method used is a quantitative method with the type of explanatory research. The location of this research is UPN "Veteran" Jakarta. The population in the study was 10,011 students using probability sampling techniques and proportional stratified sampling of 99 respondents. To find out the relationship and influence of researchers using correlation tests, coefficient of determination and regression tests. The results of this study indicate that the results of the research hypothesis prove that Ho was rejected and Ha was accepted. There was an influence of the Go Green No Campaign Message, Plastic UPN 'Veteran" Jakarta on the attitude of the use of plastic packaging in the campus environment at UPN "Veteran" students in Jakarta.